GEOSPATIAL ANALYSIS OF INTERNATIONAL COLLABORATION OF REZEKNE ACADEMY OF TECHNOLOGIES - Aleksejeva, Viktorija; Kalniņa, Laura; Kodors, Sergejs (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
The authors have completed geospatial analysis of international collaboration of Rezekne Academy of Technologies using geographical information systems.